How weak is the weakest-link principle? : On the measurement of firm owners' control rights - Alfons J. Weichenrieder; Jeremy S. S. Edwards (Center for Economic Studies and ifo Institute (CESifo), 2004)
The paper argues that the weakest link principle, which has been widely used as a measure of ultimate owners? control rights, has a number of serious problems. A theoretically more satisfactory method of measuring control rights, based on voting power indices, is proposed, and the different measures are compared using a sample of large listed German firms. The different measures produce very different results. But, whichever measure is used, taking account of pyramid ownership structures has little effect on the values of control and cashflow rights. The results also show that neither first-tier nor ultimate control rights measures are adequate on their own, suggesting that further work on ownership structure and pyramids is required to obtain satisfactory measures of large owners? control rights.
Keywords: G34; G32; 330; corporate governance; control rights; weakest-link principle; Corporate Governance; Eigentümerstruktur; Abstimmung; Macht; Schätzung; Deutschland